Comparative analysis between control actions and cervical cancer mortality in Pará between 2016 and 2021 (Research, Society and Development, 2023)
Introduction: Cervical cancer has an aggressive global incidence and high mortality in countries with insufficient control and prevention strategies. Objective: to analyze the relationship between mortality rates from cervical cancer (CC) and control strategies for this disease, in the state of Pará. Methods: This is an ecological, descriptive and time series study, using data registered in SIA/DATASUS, SISCAN and SIH/DATASUS, with data collection on primary variables being carried out from 2016 to 2021. Results: In the period analyzed, a downward trend in cytopathological exams carried out in Pará was identified, being opposite to high mortality rate from cervical cancer. More exams were carried out in the age range between 20 and 39 years old, in addition to the Lower Amazon region having the biggest decline among health regions in the same period. The variation in the mortality rate remained heterogeneous between regions, with the Baixo Amazonas and the Tocantins region showing the most significant increases. Conclusion: Mortality associated with CC, in Pará, was mainly associated with the black race and the population of elderly women, whose prevalence increased from the age of 60, in addition to the fact that the performance of oncotic Pap smear tests showed a progressive decline. between the years analyzed, indicating an association with the variation in the mortality rate.